2021
DOI: 10.1108/ijoem-03-2021-0456
|View full text |Cite
|
Sign up to set email alerts
|

Investment environment, stock market perception and stock investments after stock market crash

Abstract: PurposeThis study examines how the importance of external investment environment factors affect stock market perception, and how stock market perception affects stock investments after stock market crash witnessed by individual investors in one of the emerging stock markets.Design/methodology/approachA cross-sectional survey was administrated among 223 individual investors who experienced stock market crash in 2010–2011 in Bangladesh, and the proposed model was tested by the partial least squares-structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Lastly, Khan et al. (2021) explore the investment environment, stock market perception, and stock investments after a market crash. While not directly focused on the COVID‐19 crisis, the study provides insights into investor behavior and stock market reactions following a crash.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lastly, Khan et al. (2021) explore the investment environment, stock market perception, and stock investments after a market crash. While not directly focused on the COVID‐19 crisis, the study provides insights into investor behavior and stock market reactions following a crash.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cluster category 2 (short to medium term investment category): Innovation and technology category has a large component, is the national key support industries and fields, release of new products can be a short period of time to get a high investment income, with good growth; by the press release hot spots and industrial adjustment, suitable for short-term investment [16], combined with the results of the clustering can be seen, this category is generally the industry high-tech enterprises.…”
Section: Specific Analysis and Definition Of Stock Clustering Categoriesmentioning
confidence: 99%
“…It was found that after the stock market crisis, investors stronger considered the investment environment before making financial decisions. They assess stock market behaviour, the situation in neighbouring countries, political issues, government decisions, and economic indicators (Khan et al 2021). Wang et al (2009b) found that stocks with higher betas, higher capitalization, lower levels of illiquidity, and higher volatility in pre-crisis returns experienced a more considerable fall during the market crash itself.…”
Section: Literature Reviewmentioning
confidence: 99%